Health Relevant Behavior and its Impact on the Physician-Patient Relationship - Udo Schneider; Volker Ulrich (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
The importance of the physician-patient relationship for the health care market is beyond controversy. Recent work emphasizes a two-sided asymmetric information relationship between physician and patient. In contrast to most work looking only at the physician's perspective, our paper concentrates on the patient's view. Estimation results support the hypotheses that physician consultation and health relevant behavior are not stochastically independent. In the recursive bivariate probit model, patient's health relevant behavior has a significant influence on the probability of a physician visit. This means that health care demand and not only the contact decision is determined by both, patient and physician.
Keywords: I12; C33; D82; 330; physician-patient relationship; health behavior; bivariate probit panel